High quality implementation of 4Rs + MTP increases classroom emotional support and reduces absenteeism - Gómez, John A.; Brown, Joshua L.; Downer, Jason T. (Frontiers in Psychology, 2023)
School-based social and emotional learning (SEL) programs are associated with improvements in children’s SEL and academic outcomes, and the quality of classroom interactions. The magnitude of these effects increases at high levels of program implementation quality. This study aimed to 1) identify teachers’ profiles of quality of implementation, 2) explore teachers and classroom characteristics contributing to their propensity to comply with high quality of implementation, and 3) examine the relations between school assignment to an SEL program, quality of classroom interactions, and child SEL and academic outcomes at different levels of teachers’ compliance propensity. This study drew upon data from a cluster-randomized controlled trial evaluating the efficacy of 4Rs+MTP, a literacy-based SEL program, on third and fourth grade teachers (n = 330) and their students (n = 5081) across 60 New York City public elementary schools. Latent profile analysis indicated that measures of teacher responsiveness and amount of exposure to implementation supports contributed to the differentiation of profiles of high and low quality of implementation. Random forest analysis showed that more experienced teachers with low levels of professional burnout had high propensity to comply with high quality of implementation. Multilevel moderated mediation analysis indicated that 4Rs+MTP teachers with high compliance propensity were associated with higher classroom emotional support and lower children’s school absences than their counterparts in the control group. These findings may inform debates in policy research about the importance of providing the supports teachers need to implement SEL school programs with high quality.